Implementasi Pervasive Service Discovery Protocol pada Rumah Cerdas Berbasis NRF24L01 - Dwi Aris Suprayogi; Sabriansyah Rizqika Akbar; Mochammad Hannats Hanafi Ichsan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2017)
Smart home is one of wireless technology development. Smart home system makes devices in the home can be connected each other, so can make activity easier. One of wireless communication module which can be applied in smart home system is nRF24L01. The necessary of protocol communication and devices configuration can be said that it is not easy being a obstacle for smart home developing. Pervasive service discovery protocol method can be a solution for solving that problem. By using this method, the users doesn't need to do difficult configuration, software will search hardware and users can access service which is offered by that devices immediately. This research applies pervasive service discovery protocol method in smart home by using nRF24L01 communication module. The system is made in order to sensor node can communication as pervasive by using master node. Pervasive communication which is mentioned is a automatic addressing by system. Master node which is coordinator node will give different address to every sensor node. Based on trial which is done for 10 trial times, time needed for one sensor node to be connected with master node is 1011 ms, while time needed for two sensor nodes to be connected with master node simultaneously have average times 1011 ms and 1123.2 ms. The result of fungtional system experiment indicate that the user can monitoring and controlling device by serial monitor in master node